Health Promotion Management in the Context of Breast Cancer Prevention Using the SADARI and CERDIK Methods at Al Ihsan Regional General Hospital, West Java Province - Nurul Afidah, Syifa; Ariani, Nurul Dwi (Asian Journal of Environmental Research, 2024)
This study aims to determine the systematics of Health Promotion Management in Hospitals on the effectiveness of the performance of Hospital Health Promotion Services. By conducting studies, planning, implementation and evaluation as well as monitoring to measure the success of PKRS activities in accordance with the rules of the Regulation of the Minister of Health of the Republic of Indonesia Number 44 of 2018 concerning the Implementation of Hospital Health Promotion (PKRS). The research method used is Qualitative Descriptive with the data collection used is making questionnaires, and observations because they have close relevance to the problem. The results after collecting 20 respondents using the Pre Test revealed that the average score was 5.6 out of 100, which can be concluded that the knowledge of the hospital community is still minimal about the awareness of maintaining health with the Cerdik method and early examination of SADARI. After counseling and counseling activities with the same 20 respondents, it was seen that the increase in the number of community knowledge with an average score of 8.7 out of 100 was seen. The findings of this study show that the hospital health promotion management system has an impact on the effectiveness of educational services at Al Ihsan Hospital, West Java Province.